Lifelong and mature-onset syncope in older adults may have different mechanisms. (14th October 2021) - Torabi, P; Rivasi, G; Hamrefors, V; Sutton, R; Brignole, M; Fedorowski, A
Abstract: Background: Syncope is a common clinical problem with a sharp rise in the incidence after 70 years. In older patients, syncope is often a diagnostic challenge. It is unclear whether the age at which patients experience syncope for the first time impacts the results of syncope investigation. Purpose: To study the influence of early-onset vs. mature-onset syncope on clinical characteristics and final head-up tilt (HUT) diagnosis in a large sample of unexplained syncope patients. Methods: Consecutive patients (n=1928) with unexplained syncope after initial evaluation examined with a standard HUT protocol in a syncope unit were stratified into age groups below and above 60 years. Clinical characteristics and the final HUT diagnosis were analysed in relation to self-reported age at first syncope and age at investigation. The distribution of age at first syncope was bimodal with peaks at 15 and 70 years (Figure 1). In the present analysis, patients aged >60 years (n=836) with early-onset (<30 years) and mature-onset (>60 years) syncope were compared. Results: Vasovagal syncope (VVS) was more common in early-onset syncope, 39% vs 19% (p<0.001), (Figure 2). Orthostatic hypotension (OH) was more common in mature-onset syncope, 23% vs 7% (p<0.001), as was hypertension, 59% vs 40% (p=0.001). The frequency of carotid sinus syndrome (CSS) was not affected by age at first syncope in patients aged >60 years.Complex syncope etiology (findings suggesting overlap between VVS, OH and/or CSS) was more common among patients with early-onset syncope, 37% vs 26% (p=0.023). No definite HUT-derived diagnosis was more common in mature-onset syncope, 23% vs 13% (p=0.023). Heart failure, 9% vs 2% (p=0.024) and atrial fibrillation, 20% vs 9% (p=0.013) were more common in mature-onset syncope. Prodromes were less common in mature-onset syncope, 26% vs 52% (p<0.001), however there was no significant difference in reported palpitations preceding syncope and dizziness on standing. Conclusions: Mature-onset syncope was more often associated with absence of prodromes, orthostatic hypotension, inconclusive HUT findings and presence of heart failure and atrial fibrillation suggesting cardiac syncope to be the likely cause. Early-onset syncope was associated with presence of prodromes, vasovagal reflex mechanism and complex syncope diagnosis. Lifelong and mature-onset unexplained syncope may have different pathophysiological mechanisms in older patients and aetiologies other than vasovagal syncope should be carefully considered in patients with first-ever syncope in later life. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish heart and lung foundationCrafoord foundation